Peran Guru Pendidikan Agama Kristen Dalam Pembinaan Rohani Siswa - Heri Kiswanto (CARAKA: Jurnal Teologi Biblika dan Praktika, 2023)
The spiritual growth of students shows that there is a spiritual increase, therefore in order to get good quality students still get special spiritual guidance apart from learning. Furthermore, it is hoped that with good quality, coaching carried out routinely can influence student behavior in their daily lives. The purpose of this study is how Christian Religious Education Teachers apply forms of spiritual development that can be carried out in schools, including: First through worship together, secondly studying the Bible and fourthly making spiritual retreat activities. This model of spiritual development is very relevant to use, to be applied in school and church environments. The research method used in this research is descriptive qualitative. Where to obtain the necessary data through a literature review related to the role of Christian Religious Education teachers in the spiritual development of students. From the results of this study, it was found that the role of the Christian Religion teacher in the spiritual development of students has an influence on changes in behavior and spiritual growth in students.